Capacidade de investimento e autonomia econômica do setor público de municípios selecionados - Galdino, Rick Humberto Naves (2012)
The paper analyzes the ability of investment and economic autonomy of the public sector in cities selected according to three distinct regional economic systems. According to REGIC 2007 (IBGE, 2008) the cities are hierarchically polarized in the regions of influence of the poles of Juiz de Fora, Montes Claros and Uberlândia. The objective of this research was to investigate the relationship between public finance and investment capacity of the municipal public sector with the population and economic performance of different cities within the hierarchy of the population in the selected regions between the years of 2000 and 2010. According to the distribution models of public resources for investment in underdeveloped regions of Hirschman (1958). It was found that prevailed concentration and dispersion models for investment of resources, and the third pattern is not fulfilled, that is the development of stagnant areas. The cities structure of tax and financial powers do not allow changes in the hierarchical structure of regions, from their own budgets. Thus, the smaller cities in a situation of low growth or stagnant, depend to a greater degree than larger cities, the public policies for development. The population growth rate of the selected cities indicates an increase in inequality between the smallest and largest cities of the three selected regions in population terms, reaffirming the model hub and uneven growth of the cities. Besides, the analysis of municipal budgets is necessary to check the involvement of other spheres of government, with their budgets and their models of growth and development. Secondary data were obtained from organizations linked to governments, the Brazilian Institute of Geography and Statistics (IBGE), João Pinheiro Foundation (FJP), Institute of Applied Economic Research (IPEA).